2003
DOI: 10.1073/pnas.0630588100
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride accumulation protects against fatty acid-induced lipotoxicity

Abstract: Excess lipid accumulation in non-adipose tissues is associated with insulin resistance, pancreatic ␤-cell apoptosis and heart failure. Here, we demonstrate in cultured cells that the relative toxicity of two common dietary long chain fatty acids is related to channeling of these lipids to distinct cellular metabolic fates. Oleic acid supplementation leads to triglyceride accumulation and is well tolerated, whereas excess palmitic acid is poorly incorporated into triglyceride and causes apoptosis. Unsaturated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

117
1,471
8
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,680 publications
(1,644 citation statements)
references
References 40 publications
117
1,471
8
5
Order By: Relevance
“…The results obtained are in line with other investigations which demonstrated increase in the cell death, ceramide synthesis, and content in the liver and other cell types under the oversupply of saturated free fatty acids in the culture media (Merrill et al 1995;Wei et al 2006;Listenberger et al 2003;Blázquez et al 2000). Culturing of hepatocytes in the presence of α-tocopherol prevented the palmitate-induced cell damage.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained are in line with other investigations which demonstrated increase in the cell death, ceramide synthesis, and content in the liver and other cell types under the oversupply of saturated free fatty acids in the culture media (Merrill et al 1995;Wei et al 2006;Listenberger et al 2003;Blázquez et al 2000). Culturing of hepatocytes in the presence of α-tocopherol prevented the palmitate-induced cell damage.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have demonstrated that the ability to synthesize TAG plays a critical role in the protection from palmitate‐induced lipotoxicity (Kamili et al ., 2015; Listenberger et al ., 2003; Przybytkowski et al ., 2007). For example, oleate supplementation promotes TAG synthesis in CHO cells and also prevents palmitate‐induced apoptosis in mouse embryonic fibroblasts but this protection was not seen in DGAT1 −/− mouse embryonic fibroblasts (Listenberger et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, oleate supplementation promotes TAG synthesis in CHO cells and also prevents palmitate‐induced apoptosis in mouse embryonic fibroblasts but this protection was not seen in DGAT1 −/− mouse embryonic fibroblasts (Listenberger et al ., 2003). We demonstrate that pretreatment of MDA‐MB‐231 cells with oleate or FA mix protects from both palmitate‐induced and serum starvation‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 A tempting interpretation is that when fatty acids are stored in triglycerides they are diverted from pathways that result in cellular damage. 37 Theoretically, such an effect could be explained by the accumulation of intermediate products along the chain of de novo lipogenesis, rather than by the reduction in the endproduct (here steatosis). In any case, the MCD model barely resembles human NASH, as only hepatic but not systemic IS is present.…”
Section: Efficacy Outcomesmentioning
confidence: 99%